2009
DOI: 10.1118/1.3213453
|View full text |Cite
|
Sign up to set email alerts
|

A real‐time prostate cancer detection technique using needle insertion force and patient‐specific criteria during percutaneous intervention

Abstract: In this article, the authors present a novel real-time cancer detection technique by using needle insertion forces in conjunction with patient-specific criteria during percutaneous interventions. Needle insertion experiments and pathological analysis were performed for developing a computeraided detection ͑CAD͒ model. Backward stepwise regression method was performed to identify the statistically significant patient-specific factors. A baseline force model was then developed using these significant factors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Some other interesting effects noticed in the data include tissue inhomogeneity, tissue relaxation [20], and delayed capsule puncture [14]. Breathing effects are also present, especially for insertions into liver.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some other interesting effects noticed in the data include tissue inhomogeneity, tissue relaxation [20], and delayed capsule puncture [14]. Breathing effects are also present, especially for insertions into liver.…”
Section: Resultsmentioning
confidence: 99%
“…Our preliminary work characterized the effects of various parameters on needle curvature in ex vivo goat liver [9]. In vivo forces associated with needle insertion have been measured for human prostate [13] [14], porcine liver [15], and both porcine liver and kidney [16]. However, the needles used in these experiments were conventional stainless steel needles.…”
Section: Introductionmentioning
confidence: 99%
“…This force must then be equal to 12.6 N to reach the maximum deflection estimated previously. This value seems satisfactory, as the axial force only reaches for instance 10 N when puncturing a prostate capsule [37], and is significantly lower after this puncture.…”
Section: ) Needle Deflection-mentioning
confidence: 89%
“…Yan et al [67] demonstrated the feasibility of in vivo cancer detection in real time during prostate biopsy by observing the force patterns for tumor and normal tissue. Using a mechanical model, Beekmans et al [68] developed an FPI based fiber optic sensor to measure the Young’s Modulus of the bovine liver tissue embedded in gelatin and demonstrated its feasibility.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%